Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon - Akum, Christian; Sonnenberg, Rainer; van Der Zee, Jouke R.; Wildekamp, Rudolf H. (Zootaxa, 2007)
Fundulopanchax kamdemi, new species, is described from small swampy pools and rivulets of the Ndian and Akpa-Yafe River systems, Cameroon. F. kamdemi is distinguished from all other known Fundulopanchax species by a unique male coloration and from most congeners by a higher number of rays in dorsal and anal fins.